Tinjauan Terhadap Perkawinan Dalam Hukum Adat Batak Berdasarkan Undang- Undang Nomor 1 Tahun 1974 - Irene Gracia Simanjuntak; Silvia Angela; Moody Rizky Syailendra (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2023)
Humans were created by God Almighty as social beings who cannot live alone and need other people to live their lives. Humans will marry if the individual is able to adjust himself to a partner. The purpose of this writing is about how marriages are based on Batak customary law based on Indonesian regulations. In this scientific article the type of research used is normative research. Normative research in this scientific article uses the concepts contained in the law. The Toba Batak Customary Law System is often the concern of the Indonesian people regarding customary law that is binding on their society. In Batak marriages, it is not permissible if the bride and groom are of the same clan, this is something that is still percussion for the Toba Batak people because it is very common which can bring disaster. But along with the development of the globalization era, it is possible that there are some Batak Toba people who marry in the same clan.